Evaluation Study of the High Yielding Varieties Programme Report for the Rabi 1968-69 Wheat, Paddy and Jowar - Planning Commission (Planning Commission, 1969)
This is in continuation of our study of the H.Y.V.P. for the agricultural year 1968-69, for the kharif season of which a report was presented in June, 1969. This report is for rabi 1968-69 covering wheat, paddy and jowar. the aspects covered are the same as in the kharif season. This study was carried out in 32 development blocks and 96 sample villages covering 876 participant and 160 non-participant cultivators. The various aspects of the programme and the comparative performance have been analysed in six chapters. The seasonal conditions in Rabi, 1968-69 in the wheat growing States of Punjab, Haryana, U.P. and Rajasthan were generally favourable except for partial drought conditions in certain areas.
Programme Evaluation Organisation Planning Commission Government of India